Differences in seasons and rice varieties provide opportunities for improving nitrogen use efficiency and management in irrigated rice in Kenya - Gweyi-Onyango, J.; Ntinyari, W.; Egesa, A.O.; Mose, R.; Njinju, S.; Giweta, M.; Masso, C. (IOP Publishing, 2021)
Apart from nitrogen (N) rates, N use efficiency (NUE) (yield N/total input N) is affected by seasons, crop developmental stages, and varieties. Knowledge of how these factors affect NUE in rice production in Kenya is limited. Therefore, field experiments were conducted with 'low rates' of N (simulating farmers' practices) of 0, 26, 52 and 78 kg N ha−1 with five varieties (MWUR1, MWUR4, IRAT109, NERICA4 and NERICA10) and higher rates of N (125, 175, and 225 kg N ha−1) simulating researchers' doses with two lowland varieties (Basmati 370 and BW 196) and IR 72. Another experiment on NUE responses to sites, N rates and dose (split or full dose) was undertaken with the IR97 variety. With the 'low rate', yields increased with incremental N rates up to 52 Kg N ha−1 and declined (during cold periods, for some varieties). In this scenario, the N agronomic efficiencies (AEN) declined with increasing N but depended on sites and seasons. However, most AEN values were above 100, implying nutrient mining. In most cases (except at the Mwea site), the N utilization efficiency (NUtE) ranged from 16 to 22kg kg−1 and were not significantly affected by sources and methods of N application. In all cases, an increase in N elicited declining trends in NUtE. Moreover, N uptake efficiency ranged between 22 and 90kg kg−1 without significant variation among varieties. For the 'high N rates', high biomass yield resulted in higher grain yields in BW 196 and IR 72 but yield declined beyond 75 kg ha−1 N rates due to poor grain filling, particularly when a cold period coincided with booting and grain filling. We conclude that N rates, doses and rice varieties are key determinants of AEN and NUtE in contrasting rice growing seasons in Kenya. Cropping seasons and rice varieties are therefore potential key determinants of sustainable rice productivity and improved NUE in rice-based systems in the studied regions of Kenya.